Macroeconomic Effects of Dividend Taxation with Investment Credit Limits - Ghilardi, Matteo; Zilberman, Roy.. (Washington, D.C. : International Monetary Fund, 2022)
We analyze the effects of dividend taxation in a general equilibrium business cycle model with an occasionally-binding investment credit limit. Permanent dividend tax reforms distort capital investment decisions in the binding long-run equilibrium, but are neutral otherwise. Temporary unexpected tax cuts stimulate shortterm real activity in the credit-constrained economy, yet produce contractionary macroeconomic outcomes in the slack regime. The occasionally-binding constraint reconciles the `traditional' and `new' views of dividend taxation, and highlights the importance of measuring the firm's initial borrowing position before enacting tax reforms. Finally, permanently lower dividend taxes dampen financial business cycles, and help to explain macroeconomic asymmetries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Capacity; Capital; Financial Markets and the Macroeconomy; Intangible Capital; Investment